2010
DOI: 10.1007/s12199-010-0162-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of health-related quality of life using EQ-5D in Takamatsu, Japan

Abstract: Objectives Healthy Japan 21 (Japanese National Health Promotion in the 21st Century) was started in 2000 to promote extension of healthy life expectancy and improve health-related quality of life (HRQOL). The present study aims to describe HRQOL of Japanese subjects using the EuroQol questionnaire (EQ-5D) and investigate the influence of social background, health-related behaviors, and chronic conditions on HRQOL using representatives in Takamatsu, Japan. Methods Data were obtained from a 2005 Takamatsu City h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
24
5
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 29 publications
21
24
5
4
Order By: Relevance
“…Our results are consistent with those of previous studies in the literature, which have described depression as a major factor, along with chronic diseases, associated with reduced QoL. 9,12,22,23 Population-based surveys 10,11,[23][24][25] using the EQ-5D instrument have detected an impact for diabetes, depression, and respiratory disorders. Even though the impact for respiratory disorders was not significant in the present study, our structured questionnaire included a large spectrum of self-reported respiratory conditions (asthma, bronchitis, or any other respiratory disorder), which could hypothetically explain this difference in relation to other populationbased studies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results are consistent with those of previous studies in the literature, which have described depression as a major factor, along with chronic diseases, associated with reduced QoL. 9,12,22,23 Population-based surveys 10,11,[23][24][25] using the EQ-5D instrument have detected an impact for diabetes, depression, and respiratory disorders. Even though the impact for respiratory disorders was not significant in the present study, our structured questionnaire included a large spectrum of self-reported respiratory conditions (asthma, bronchitis, or any other respiratory disorder), which could hypothetically explain this difference in relation to other populationbased studies.…”
Section: Discussionsupporting
confidence: 91%
“…25 In terms of sociodemographic characteristics, the associated factors are also consistent with those reported by other studies, reflecting changes in the perception of individuals regarding their HRQoL. 7,9,10,22 For the findings about living in the satellite towns, we could hypothesize that the disparities are enhanced by more precarious urban infrastructure, lower incomes, higher levels of violence, and commuting time, considering that more than half of the residents do not work in the area where they live. 27 One strength of the present study is that the HRQoL of adults living in Brasília was measured by a tool validated for the Brazilian context.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We also added regular weekly physical activities (≥1 per week moderate or vigorous exercises), a lifestyle indicator, into the analyses, which has been commonly used in HRQOL studies [41]. …”
Section: Methodsmentioning
confidence: 99%
“…Population norms for the EQ-5D-3L index scores have been reported in the USA [31], Switzerland [32], Demark [33], Portugal [34], Australia [35], Taiwan [36], Singapore [37,38], Sri Lanka [39], and Japan [40,41]. No population norms for the EQ-5D-3L index scores have been reported in China.…”
Section: Introductionmentioning
confidence: 99%